Islamic Leadership, Workplace Spirituality, and Innovative Work Behavior on Teachers’ Islamic Performance: Mediating Role of OCBIP - Nur Rahmi Sonia; Sutiah; Wahidmurni; Soeharto (Cendekia: Kependidikan dan Kemasyarakatan, 2024)
This research aims to analyze the influence of Islamic leadership, workplace spirituality, and innovative work behavior on teachers’ Islamic performance through Organizational Citizenship Behavior Islamic Perspective (OCBIP) mediation. This research employed a quantitative approach with a correlational type. The population of this research was all certified teachers in Madrasa Aliyah Ponorogo, Indonesia. The total sample involved was 276 certified teachers. This study employed the proportional stratified random sampling technique. The data were collected directly from respondents. The analysis in this study used Partial Least Square. The research findings reveal that OCBIP mediates the influence of Islamic leadership and workplace spirituality on teachers’ Islamic performance but fails to mediate the influence of innovative work behavior on teachers’ Islamic performance. Hence, the present study offers an essential contribution to the Islamic management literature by showing the mediating role of OCBIP in the relationship between leadership spirituality and performance, as well as providing practical insights for developing educational policies that are more holistic and with Islamic values.